Understanding of Postmortem Examination and Disinterest Among Medical Students (The Planet, 2024)
Background: Autopsies, which are critical for determining the cause of death, understanding how diseases progress, and improving medical practices, have been performed less frequently around the world in recent years. This decline has raised concerns about the impact on medical training, the quality of healthcare, and the advancement of medical knowledge, potentially hindering the development of future medical professionals. Aim of the study: This study assessed medical students’ knowledge, attitudes, and reasons for disinterest in postmortem examinations and morbid anatomy specialization, aiming to identify factors influencing their perceptions and career choices. Methods & Materials: A descriptive cross-sectional study was conducted among 150 third-year medical students. Data was collected using a structured questionnaire designed to evaluate understanding of autopsy procedures, attitudes towards autopsy, and reasons for not choosing morbid anatomy. The collected data was analyzed using SPSS version 26 to identify key trends and associations. Result: Students demonstrated understanding of the legal and procedural importance of autopsies in medical practice, but significant misconceptions and discomfort persist regarding certain aspects. Discomfort with dissecting dead bodies and the perception of autopsies as a dirty procedure were major reasons for disinterest in pursuing morbid anatomy specialization among the students. Conclusion: Medical students acknowledge the essential role of autopsies in medical education, but misconceptions and discomfort persist, highlighting the need for targeted educational interventions. The limited sample diversity and reliance on questionnaires restricts the generalizability and depth of findings, indicating a need for future research with broader samples and mixed-methods approaches.
Keywords: Autopsy; Medical Education; Knowledge; Attitude; Misconceptions; Discomfort